The retention difference between cobalt chromium and zirconia coping in different angulations on telescopic overdenture - Kevin Christopher Kawilarang; Heriyanti Amalia Kusuma; Murti Indrastuti (Majalah Kedokteran Gigi Indonesia, 2020)
Telescopic overdenture is one type of removable denture that uses dual coping system that consists of primary and secondary coping. Retention of telescopic overdenture is obtained from the friction between primary and secondary coping, which is mainly influenced by the type of material and coping angulation. The purpose of this study is to determine the retention differences between CoCr and zirconia coping with 0Â°, 1Â°, and 2Â° angulations. Twenty four pairs of telescopic overdenture coping samples with 6 mm length were divided into 6 groups (n = 4), CoCr 0°, CoCr 1°, CoCr 2°, zirconia 0°, zirconia 1°, and zirconia 2°. Measurement of retention between coping is done by pull-off test using universal testing machine (UTM) and data were analyzed by two way ANOVA. The results showed that the largest average retention was found in zirconia coping with 0° angulation group (22.48 N), while the smallest average retention was found in CoCr coping with 2° angulation group (10.28 N). Two way ANOVA revealed that there were significant differences among groups (p<0.05). LSD tests showed that there were significant differences among all of groups. This study concludes that zirconia coping has higher retention than CoCr coping and coping with 0° angulation has the highest retention.